Combating H7N9: an interview with Lanjuan Li and Yi Shi. Issue 3 (24th August 2015) - Xu, Xiuling
Abstract: On March 31, 2013, the Chinese government reported that three persons from Shanghai and Anhui had died from a novel avian influenza virus, known as H7N9. This avian flu is unique in that it has a high human mortality rate, while fatality in poultry remains low. In other words, this virus can circulate 'silently' among poultry, but be a very possible cause of the next flu pandemic. Since 2013, human cases of H7N9 infection have been reported continuously, posing a potential threat to public health in China and attracting global attention. Will H7N9 be the next flu pandemic? With this question, NSR spoke to clinical expert, Professor Lanjuan Li from Zhejiang University, and the virologist, Dr. Shi Yi, from the Beijing Institutes of Life Science, Chinese Academy of Sciences and Shenzhen Third People's Hospital. In this interview, they share with us the biological information of H7N9, its clinical manifestation and treatment, and its future pandemic potential.